The effect of 8-weeks of combined resistance training and chocolate milk consumption on maximal strength, muscle thickness, peak power and lean mass, untrained, university-aged males - Yapici, Hakan; Gülü, Mehmet; Yagin, Fatma Hilal; Ugurlu, Dondu; Comertpay, Ertan; Eroglu, Oguz; Kocoğlu, Melike; Aldhahi, Monira I.; Karayigit, Raci; Badri AL-Mhanna, Sameer (Frontiers in Physiology, 2023)
The overarching aim of this study was to investigate the combined effects of chocolate milk consumption (500 mL) with 8-week of resistance training on muscle hypertrophy, body composition, and maximal strength in untrained healthy men. A total of 22 Participants were randomly divided into two experimental groups: combined resistance training (3 sessions per week for 8 weeks) and chocolate milk consumptions (include 30 g protein) Resistance Training Chocolate Milk (RTCM) (Age: 20.9 ± 0.9 years old) and resistance training (RT) only (Age: 19.8 ± 0.7 years old). Muscle thickness (MT), using a portable ultrasound, body composition, body mass, maximal strength (one repetition maximum (1RM), counter movement jump (CMJ) and peak power (PP) were determined at baseline and 8 weeks later. In the RTCM, finding showed a significant improvement in the outcomes compared to the RT group, besides the main effect of time (pre and post). The 1RM total increased by 36.7% in RTCM group compared to 17.6% increased in the RT group (p < 0.001). Muscle thickness increased by 20.8% in the RTCM group and 9.1% in the RT group (p < 0.001). In the RTCM group, the PP increased by 37.8% compared to only 13.8% increase in the RT group (p = 0.001). The group*time interaction effect was significant for MT, 1RM, CMJ, and PP (p < 0.05), and it was observed that the RTCM and the 8-week resistance training protocol maximized performance. Body fat percentage (%) decreased more in the RTCM (18.9%) group than in the RT (6.7%) group (p = 0.002). In conclusion, chocolate milk (500ml) with high protein content consumed in addition to resistance training provided superior gains in terms of MT, 1RM, body composition, CMJ, and PP. The finding of the study demonstrated the positive effect of casein-based protein (chocolate milk) and resistance training on the muscle performance. Chocolate milk consumption has a more positive effect on muscle strength when combined with RT and should be considered as a suitable post-exercise nutritional supplement. Future research could be conducted with a larger number of participants of different ages and longer study durations.